2000
DOI: 10.1093/gerona/55.12.m740
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm Abnormalities of Wrist Activity of Institutionalized Dependent Elderly Persons With Dementia

Abstract: This four-category classification system provides a scientific approach for studying the mechanisms of circadian activity rhythm abnormalities of elderly persons with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 6 publications
0
7
0
2
Order By: Relevance
“…A recent 24-hour actigraphic study performed in institutionalized dementia patients showed four types of abnormal rhythms: a free-running (phase-delayed) type, an aperiodic type, an ultradian rhythm type with a cycle lasting 3 to 4 hours, and a flattened amplitude type in which patients were largely bedridden. 4 Sundowning defines the tendency of demented people to nocturnal agitation. Sundowning can be a primary factor leading to the decision to institutionalize a patient.…”
Section: Insomnia In Neurological Diseases (Degenerative and Others)mentioning
confidence: 99%
“…A recent 24-hour actigraphic study performed in institutionalized dementia patients showed four types of abnormal rhythms: a free-running (phase-delayed) type, an aperiodic type, an ultradian rhythm type with a cycle lasting 3 to 4 hours, and a flattened amplitude type in which patients were largely bedridden. 4 Sundowning defines the tendency of demented people to nocturnal agitation. Sundowning can be a primary factor leading to the decision to institutionalize a patient.…”
Section: Insomnia In Neurological Diseases (Degenerative and Others)mentioning
confidence: 99%
“…They encompass sleep disorders such as sleep-disordered breathing (SDB) [3], insomnia [4] and desynchronization of the chronobiological sleep cycle [5,6], as well as behaviours disrupting nocturnal sleep, such as agitation, physical aggression, loud vocalizations and wandering [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Its main weakness is that it underestimates high nocturnal agitation in some cases. These results depend on the system's calibration; thus, activity measured using other systems could differ 5 . The nurses were easily able to integrate this scale in their routine patient assessment.…”
Section: Discussionmentioning
confidence: 99%